Molecular and macromolecular diffusion in human meniscus: relationships with tissue structure and composition. Issue 3 (March 2020) - Travascio, F.; Devaux, F.; Volz, M.; Jackson, A.R.
Summary: Objective: To date, the pathophysiology of the meniscus has not been fully elucidated. Due to the tissue's limited vascularization, nutrients and other molecular signals spread through the extracellular matrix via diffusion or convection (interstitial fluid flow). Understanding transport mechanisms is crucial to elucidating meniscal pathophysiology, and to designing treatments for repair and restoration of the tissue. Similar to other fibrocartilaginous structures, meniscal morphology and composition may affect its diffusive properties. The objective of this study was to investigate the role of solute size, and tissue structure and composition on molecular diffusion in meniscus tissue. Design: Using a custom FRAP technique developed in our lab, we measured the direction-dependent diffusivity in human meniscus of six different molecular probes of size ranging from ∼300Da to 150, 000Da. Diffusivity measurements were related to sample water content. SEM images were used to investigate collagen structure in relation to transport mechanisms. Results: Diffusivity was anisotropic, being significantly faster in the direction parallel to collagen fibers when compared the orthogonal direction. This was likely due to the unique structural organization of the tissue presenting pores aligned with the fibers, as observed in SEM images. Diffusion coefficients decreased as the molecular size increased, following the Ogston model. No significant correlations were found among diffusion coefficients and water content of the tissue. Conclusions: This study provides new knowledge on the mechanisms of molecular transport in meniscal tissue. The reported results can be leveraged to further investigate tissue pathophysiology and to design treatments for tissue restoration or replacement.